Does indocyanine green fluorescence angiography impact the intraoperative choice of procedure in free vascularized medial femoral condyle grafting for scaphoid nonunions? - Mulica, Markus; Horch, Raymund E.; Arkudas, Andreas; Cai, Aijia; Müller-Seubert, Wibke; Hauck, Theresa; Ludolph, Ingo (Frontiers in Surgery, 2022)
Background: Free vascularized medial femoral condyle (MFC) bone grafts can lead to increased vascularity of the proximal pole and restore scaphoid architecture in scaphoid non-unions. The intraoperative perfusion assessment of the bone graft is challenging, because conventional clinical examination is difficult. Indocyanine green angiography (ICG) has previously shown to provide real-time intraoperative evaluation of soft tissue perfusion in reconstructive surgery. The present study investigated the utility of ICG-angiography in patients treated with a free medial femoral condyle graft for scaphoid non-union. Methods: We performed a retrospective analysis of patients with non-union of the scaphoid, in which ICG-angiography was used intraoperatively for perfusion assessment. For all patients medical records, radiographs, intraoperative imaging and operative reports were reviewed. Intraoperative ICG-dye was administered intravenously and laser angiography was performed to assess bone perfusion. Scaphoid union was examined with postoperative CT-scans. Results: Two of the patients had documented osteonecrosis of the proximal pole at the time of surgery. Four patients received a non-vascularized prior bone graft procedure and in one patient a prior spongiosa graft procedure was performed. The mean time from injury to the MFC bone graft surgery was 52.7 months, and the mean time from prior failed surgery was 10.4 months. Perfusion of the vascular pedicle of the MFC and of the periosteum could be detected in all patients. In 2 patients even perfusion of the cancellous bone could be demonstrated by ICG-angiography. Following transplantation of the bone graft patency of the vascular anastomosis and perfusion of the periost was confirmed by ICG-angiography in the assessed cases. No additional surgery regarding a salvage procedure for a scaphoid non-union advanced collapse was necessary in the further course. Conclusion: ICG-angiography has shown to be a promising tool in the treatment of scaphoid non-union with medial femoral condyle bone grafts. It enables intraoperative decision making by assessment of the microvascular blood supply of the periosteum and the vascular pedicle of the MFC bone graft. Further studies need to evaluate the impact on union rates in a long term follow up.